WEIGHTED INDICATORS OF SMALL ISLAND SETTLEMENT ENVIRONMENTAL QUALITY IN KEPULAUAN SERIBU USING ANALYTIC HIERARCHY PROCESS (JURNAL SPASIAL, 2021)
Small island territories are generally more vulnerable than the mainland, especially from environmental disasters that are not easily recovered.  Moreover, the importance of a decent and healthy living environment for humans in urban and rural, inlands or small islands, including slum and informal-settlement was for the sake of people's well-being, a better quality of life, and sustainable human settlements. Therefore, it is important to have a model for the assessment of settlement environment quality specifically on small islands that takes into consideration many important indicators and how much influence each of these indicators has. So, this paper studies the use of the Analytic Hierarchy Process (AHP) to find out the weight of indicators that influence the settlement environmental quality on small islands in Kepulauan Seribu. The total number of indicators listed was 45 indicators from 16 criteria and four aspects. The groups of respondents (local governments and community groups (RW)) gave some interesting results as their different weight priority on some indicators. And at the end, the result could be developed into a small island settlement environmental quality index to assess small island settlement environmental quality and to understand the condition of small islands in the location in Kepulauan Seribu.